Peningkatan Kapasitas Pengelolaan Keuangan UMKM melalui Pelatihan Pembukuan, Laporan Keuangan Sederhana, dan Analisis Biaya Desa Batumarta 1 Kecamatan Lubuk Raja - Miftah Khoirunnisa; Eka Ratna Saputri; Ally Roni; Sulia Ningsih (Lembaga Pengembangan Kinerja Dosen, 2026)
This Micro, Small, and Medium Enterprises (MSMEs) empowerment and development program aims to improve the capacity of business financial management through training in simple bookkeeping, preparation of simple financial reports, and business cost analysis in Tegal Sari Hamlet, Block S, Batumarta 1 Village, Lubuk Raja District, Ogan Komering Ulu Regency. This program is motivated by the low ability of MSMEs to systematically record their finances, separate their business finances from their personal finances, and utilize cost information as a basis for business decision-making. The implementation method includes an initial survey, observation, interviews, training, and direct mentoring for MSMEs. The results of the program indicate that before the program was implemented, most MSMEs had not implemented regular financial records and had not prepared business financial reports. After the training and mentoring, there was an increase in the understanding and skills of MSMEs in recording daily financial transactions, preparing simple profit and loss reports, and calculating the cost of production as a basis for determining selling prices. This activity has a positive impact on increasing the independence and sustainability of MSME business management.